PENGARUH DISIPLIN DAN KEPEMIMPINAN TERHADAP MOTIVASI KERJA PEGAWAI DENGAN KESEJAHTERAAN SEBAGAI VARIABEL MODERASI - Handayaningsih, Kus -; -, Ernawati - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2012)
ABSTRACT The purpose of this study was to: (1) analyze the significance of the influence of discipline on employee motivation, (2) analyze the significance of the influence of leadership on employee motivation, (3) analyze the significance of the welfare effects on employee motivation, (4) analyze the significance of the influence of discipline employee motivation are moderated by the variable welfare, and (5) analyze the significance of the influence of leadership on employee motivation are moderated by welfare variables. Research sites in the Health Office of Boyolali. The research population is all employees totaling 85 people comprising 77 civil servants and 8 Employee Variable (PTT). Study sample as many as 85 respondents with a total sampling technique. Types of data using qualitative data and quantitative data. Sources of data using primary data and secondary data. Data collection techniques using documentation, observation and questionnaires. The analysis technique uses test validity, test reliability classical assumption test, linear regression, t test, F test, the coefficient of determination and absolute difference test. The results showed that (1) there is a significant influence employee motivation discipline, (2) there is a significant effect of leadership on employee motivation, (3) there is a significant effect on motivation employee welfare, (4) moderate the influence of disciplinary welfare on employee motivation obtained p value (0.019) <0.05 so the hypothesis that welfare moderating influence employee motivation discipline, (5) welfare moderating influence of leadership on employee motivation Health Office of Boyolali. Keywords: discipline, leadership, wealth, work motivation